Are campus food environments healthy? A novel perspective for qualitatively evaluating the nutritional quality of food sold at foodservice facilities at a Brazilian university. (March 2017) - Pulz, Isadora Santos; Martins, Paula Andréa; Feldman, Charles; Veiros, Marcela Boro
Aims: The purpose of this novel study was to evaluate the food environment at a Brazilian university, encompassing 6 restaurants and 13 snack bars. The investigation uniquely analyses the food environment (barriers, facilitators, type of foods and prices). This was a food-based analysis of the nutritional quality of the products sold on campus. Methods: A cross-sectional descriptive design was used, applying the classic Nutrition Environment Measures Survey–Restaurants (NEMS-R) adapted for Brazil and an original methodology to evaluate and classify qualitatively the nutritional quality and characteristics of the food. A census of all campus food environments was applied. Results: The main results show most food and beverage products were made with processed ingredients and had a lower nutritional quality and price when compared with similar products made on premises, that is, processed iced tea compared with fresh tea ( p  < .001), fried refined flour salgados compared with baked wholegrain flour salgados ( p  < .001) and refined flour biscuits compared with those made with whole grains ( p  = .028). Only 16% of the outlets provided food ingredients or nutritional information of products available. Conclusion: The overall options for healthy food choices and good nutritional quality on campus were mostly limited by the availability and higher prices of products. These findings could be used to develop new policy perspectives for the offering of healthy food items and to facilitate better food choices among students in a healthier food environment.